Science Biology Digital Video: Reproductive Health Education for Pre-School Children - Novita; Eny Constant Tia Zaenal Arifin; Desi Kurnia Yuli Susanti; Fida Fauziyah Istiqomah; Hanny Rohmatul Hafidah (Postgraduate, University of Mataram, 2023)
The purpose of this study was to determine the effectiveness of the video method and fairy tales on changes in knowledge about reproductive health of sexual violence in pre-school children in TK District in 2023. The research method conducted was to use quasi experimental with purposive sampling with a sample of 120 people. Data techniques included in univariate analysis using frequency distribution and bivariate analysis using statistical calculations of the SPSS program. At Al-Hanif Islamic Kindergarten, the sig value was obtained. (2-tailed) 0.001 in video intervention and 0.000 in fairy tale intervention. In Kartini Kindergarten, the sig. (2-tailed) 0.000 on video intervention and 0.000 on fairy tale intervention. At RA Al-Barokah Kindergarten, the sig. (2-tailed) 0.001 in video intervention and 0.001 in fairy tale intervention. At Az-Zahra Kindergarten, the sig. (2-tailed) 0.001 in video intervention and 0.001. From the significant results in the four kindergartens, it is known that the significant value is less than 0.05. Thus it can be seen that there is an influence in using video and fairy tale methods on pre-school children's knowledge about sexual violence. Based on the results of the Independent sample t-test, the four kindergartens have a sig. (2-tailed) which is <0.05. This shows that there is a difference in effectiveness between video and fairy tale methods on the level of knowledge of pre-school children.